The academic motivation of primary school students who use electronic games - Mihbas, Nidaa Shaker (Al-Adab Journal, 2022)
The current research aims to: 1- Knowing the academic motivation of primary school students who use electronic games. 2- Knowing the significance of the differences in the academic motivation of primary school students who use electronic games according to gender (males - females). In order to achieve this, the researcher has built a scale of the academic motivation for primary school students who use electronic games according to the theory of motivation (Prensky). After verifying the accuracy of the psychometric properties of the research scale and its paragraphs, the research scale was applied to the research sample and the data was analyzed using the Statistical Package for Social Sciences (SPSS) and the results showed the following: First: The weakness of the academic motivation of primary school students who use electronic games. Second: - There are no statistically significant differences in the academic motivation of primary school students who use electronic games according to the gender variable (male - female).